Observational Study of Fetal Monitoring in Different Maternal Positions at More Than 3600 Masl Huancavelica, 2021 - Cardenas Pineda, Lina Yubana (2023)
This research aims to determine the effect of maternal left lateral decubitus and Fowler positions on electronic fetal monitoring at more than 3600 Masl-Huancavelica, 2021. Method: the research was pre-experimental, prospective, and longitudinal analytical; the level of research is explanatory; normality was evaluated with the Shapiro-Wilk statistician and statistical analysis with the Wilcoxon signed-rank test sample: 35 pregnant women between 32 and 42 weeks. Each one underwent two NST of 20 minutes (LLD and Fowler). Results: the average age was 25 years old and a mean of 37.26 weeks of gestational age; 37.1% were primigravida, 42.9% second gestation and 20% multiple gestations; in the NST in the LLD position, it was found: that 91.4% reactivity, 8.6% non-reactive, there were no pathological, while in the Fowler position: 74.3% presented reactivity, 20.0% non-reactive and 5.7% pathological. The baseline in LLD was 136.06, compared to 139.31 in Fowler. The mean of variability and accelerations was 10.51 and 4.49 in LLD and 9.63 and 3.43 in Fowler; few NSTs were identified with mild variable decelerations of 0.34 and 0.09, and fetal movements were 13.11 and 10.40, respectively. There is a significant difference in the baseline, showing less in LLD (“p” value 0.000). Conclusions: The LLD position shows better results than the non-stress test; a significant difference has been found in the baseline, while the variability, acceleration and movements are similar in both positions with a significance of 0.05.